Sistem Pendukung Keputusan Pemilihan Kegiatan Ekstrakurikuler Siswa Dengan Metode Smart: Decision Support System for Selecting Student Extracurricular Activities Using the SMART Method - Sutami, Sutami; Nuswantoro, Setio Ardy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Decision-making is an essential process, especially for middle school students in selecting extracurricular activities that match their interests and talents. SMPN 1 Kahayan Hilir requires every student to participate in at least one extracurricular activity. However, many students struggle to make the right choice. To address this issue, this study develops a Decision Support System (DSS) using the Simple Multi-Attribute Rating Technique (SMART) method, which provides recommendations based on specific criteria. This research was conducted through observation, interviews with school officials, and literature studies. The criteria used in this system include talent, interest, experience, achievement, facilities, and travel distance, with respective weights of 30, 26, 18, 13, 9, and 4. The collected data is processed using the SMART method, where each extracurricular alternative is assigned a score based on normalized criterion weights. The system is developed as a web-based application using PHP and MySQL and is designed with the Unified Modeling Language (UML) to help users better understand the system workflow. The results show that this system can provide objective and efficient extracurricular recommendations. With this system, students can more easily determine extracurricular activities that align with their preferences, while school administrators can utilize it as a tool for managing extracurricular programs.